THE TEACHERS' CLINIC. - Carson, A. B.; Perry, Kenneth W.; Walker, Lauren M.; Brummet, R. Lee; Homburger, Richard H. (The Accounting Review, 1957)
Abstract When a student enrolls in one of our classes we feel, as we are sure you do if you are a teacher, that we have an obligation to give him everything, accounting- wise, that one can during the time in which he is with others. In fact we feel that this obligation or responsibility encompasses not only the student but also his parents, the accounting department, the university, the state and last but not least the accounting profession. People feel sure that in many instances the use of visual aids helps in fulfilling this obligation. Not only are such aids frequently time-saving in the presentation of a given amount of information, but also they often permit one to present a greater quantity of information and, at the same time, more up-to-date information. Transparency projection, although one of the newest types of projection, is, in many instances, rapidly becoming one of the most popular. This type of projection, which is basically the same as that frequently used in bowling alleys whereby scores are grease-pencilled on transparent sheets and projected upon a screen, often provides an instructor with many opportunities for imparting more information in less time.